Modernization of Nahdlatul Ulama Education Curriculum: Integrating Ahlussunnah Wal Jama’ah Values with Technological Innovation - Baihaqi, Ahmad; Miskiyah , Azah Zakiyatul (Al Ulya: Jurnal Pendidikan Islam, 2025)
The development of information and communication technology requires educational institutions, including those based on Nahdlatul Ulama (NU), to modernize their curricula without losing their traditional values. This article aims to examine how Ahlussunnah wal Jama'ah (Aswaja) values can be harmoniously integrated with technological innovations in the NU education system. This study uses a descriptive qualitative approach with a case study at Madrasah Tsanawiyah Ihyaul Ulum Gresik. Using primary sources from direct observation in the field, interviews with the principal, teachers, and students, and secondary sources from curriculum documents and academic literature relevant to the research theme, the data was analyzed using the Miles and Huberman analysis technique, namely through the stages of data reduction, data presentation, and conclusion drawing. Through these stages, the results of the study show that the modernization of the NU curriculum can be carried out through the integration of the values of moderation, tolerance, balance, and justice with digital technologies such as E-learning and Madrasah Digital Report Cards (RDM). Despite facing challenges such as infrastructure limitations, digital literacy, and human resource readiness, NU educational institutions have proven capable of adapting to the digital era without sacrificing their religious identity. This integration creates an adaptive, contextual, and Islamic character education model while strengthening NU's existence in responding to the challenges of the times.